2017
DOI: 10.1007/s12529-017-9672-1
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Experiences of Childbirth in Serbian Public Healthcare Institutions: a Qualitative Study

Abstract: The present study emphasized a supportive and caring relationship with medical practitioners, as well as allowing women to be more involved into their birthing process, as crucial for positive experience of birth, which might have profound and long-lasting psychosocial consequences. Recommendations for policy makers and future research are offered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 46 publications
0
34
0
3
Order By: Relevance
“…In many studies, it was stated that those who had the low level of education and income, had no social security, migrated due to a war and natural disasters, had language problems and cultural differences perceived their birth highly traumatic [7,29,31,38]. However, in Stankovicin's study, it was reported that those with the higher educational level perceived birth more negatively [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In many studies, it was stated that those who had the low level of education and income, had no social security, migrated due to a war and natural disasters, had language problems and cultural differences perceived their birth highly traumatic [7,29,31,38]. However, in Stankovicin's study, it was reported that those with the higher educational level perceived birth more negatively [4].…”
Section: Discussionmentioning
confidence: 99%
“…Positive or negative perception of this experience may vary, based on mother/family (such as individual, social and cultural reasons), the attitudes and behaviors of the health personnel who assist the birth, the interventions at birth [2][3][4], types of delivery, the facilities of the unit/place of birth (such as home, hospital), previous birth experience, birth stories and whether the current pregnancy is in low-high risk groups [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, this reduces complex reproductive phenomena to biological processes, depriving women from the full range of choices potentially available to them and from the feelings of control over their bodies and their lives that comes with exercising choice. This can be accompanied with insensitivity to the experiential and emotional aspects of reproductive events [3] or with ignoring the multiple empowering or oppressive meanings surrounding them [4]. In other cases, communication is muted and women's concerns are silenced due to fear and concern for others [5], taboos about sexual topics and behaviors such as menstruation, sexuality [6], and condom use negotiation [7], with potential implications for well-being and safety.…”
Section: Introductionmentioning
confidence: 99%
“…Stankovic [3] interviewed Serbian women who gave birth for the first time in Serbia. She uncovered how this experience, usually constructed as Bnatural^and normative, is situated in local understanding and practices.…”
Section: Introductionmentioning
confidence: 99%